2021
DOI: 10.1093/mnras/stab2808
|View full text |Cite
|
Sign up to set email alerts
|

Protruding bullet heads indicating dark matter pull

Abstract: A clump moving through the intracluster medium of a galaxy cluster can drive a bow shock trailed by a bullet-like core. In some cases, such as in the prototypical Bullet cluster, X-rays show a gas bullet with a protruding head and pronounced shoulders. We point out that these features, while difficult to explain without dark matter (DM), naturally arise as the head of the slowed-down gas is gravitationally pulled forward toward its unhindered DM counterpart. X-ray imaging thus provides a unique, robust probe o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The later cases show the offset between BEC dark matter and the cloud of baryons, so as the bullet shape of the gas that have been investigated at the Bullet-Cluster scale (see e.g. (Keshet et al 2021)).…”
Section: Head-on Collisionmentioning
confidence: 91%
“…The later cases show the offset between BEC dark matter and the cloud of baryons, so as the bullet shape of the gas that have been investigated at the Bullet-Cluster scale (see e.g. (Keshet et al 2021)).…”
Section: Head-on Collisionmentioning
confidence: 91%
“…Therefore, they are an excellent laboratory to investigate properties of the key constituents of clusters, namely the intracluster medium gas (ICM; e.g. Keshet et al 2021), the galaxies (e.g enhancement/quenching of star formation; Kelkar et al 2020;Hernández-Lang et al 2021), and the dark matter (e.g. Fischer et al 2021), even if they are observed at late stages of a merger (e.g., Tam et al 2020).…”
Section: Introductionmentioning
confidence: 99%